Tindak Pidana Penodaan Agama di Indonesia (Kajian Kasus Syiah Sampang dan Gafatar Aceh) - Binsar Zaroha Ritonga; Y.A Triana Ohouwutun (Universitas Jember, 2021)
Religion as the lantern of human life teaches various forms of kindness and the value of compassion to all mankind. Without discriminating against the religions adhered to by Indonesian law, it provides protection for religious adherents to practice religion in accordance with what they believe. Religion itself is full of moral values ​​and its eternal value, there are still some people who try to demean, abuse and tarnish religious values. The law moves when there is a human interest that is violated by another human, in this case someone's religious belief is disturbed by another. Article 156a KUHP specifically provides legal protection for anyone who feels disturbed by their sense of comfort in carrying out their religion, both worship activities and other supporting activities in carrying out religion. Article 156a is still far from perfect for providing protection to all religious adherents. There are still differences in the application of the non-criminal element in determining a defendant legally and convincingly committing religious blasphemy to be a problem that must be resolved for academics and norm-makers. The difference in determining the element of a crime occurs in Sampang and Banda Aceh. The element of a criminal act is an important element in determining whether a person has legally and convincingly committed a criminal act or not. The element of a criminal act consists of two elements, namely the subjective element and the objective element, each of which is independent and cannot be combined into one element. The panel of judges combining two elements of a criminal act is deemed inaccurate in providing legal considerations for the accused. Hope for academics and norm-makers to continue to study this blasphemy problem so that it is expected to be able to provide justice, certainty and legal benefits for all people.